The summer garden - Woods, Sherryl (Don Mills, Ontario : Mira Books, 2012)
When "Maddening Moira" O'Malley, the woman with whom he had a fling during his Dublin holiday, pays a surprise visit to Chesapeake Shores, Luke O'Brien is unsure if he is ready for a long-term relationship, forcing Moira to do some soul-searching of her own.
Includes questions for discussion.
Keywords: Man-woman relationships -- Fiction; Bed and breakfast accommodations -- Fiction; Chesapeake Bay Region (Md. and Va.) -- Fiction; Love stories